2011
DOI: 10.3928/00220124-20101201-04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Spirituality Training Program on the Spiritual and Psychosocial Well-Being of Hospital Middle Manager Nurses in Korea

Abstract: The program was effective in improving psychosocial and spiritual well-being of middle manager nurses. Thus, this program could be a resource for continuing education and staff development offerings to enhance the well-being of nurses and the spiritual care of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 31 publications
6
67
0
Order By: Relevance
“…Future research efforts must also be directed toward women and recent cohorts of returning Veterans from Iraq or Afghanistan to synthesize research with all eras of Veterans for patterns of similar reactions. Nevertheless, similar mantram stories describing the effect of calming and letting go of negative feelings have been found in other studies conducted in Veterans without PTSD [18], in adults living with human immunodeficiency virus [19], in family caregivers of Veterans with dementia [34], and in healthcare workers [35][36].…”
Section: Discussionsupporting
confidence: 72%
“…Future research efforts must also be directed toward women and recent cohorts of returning Veterans from Iraq or Afghanistan to synthesize research with all eras of Veterans for patterns of similar reactions. Nevertheless, similar mantram stories describing the effect of calming and letting go of negative feelings have been found in other studies conducted in Veterans without PTSD [18], in adults living with human immunodeficiency virus [19], in family caregivers of Veterans with dementia [34], and in healthcare workers [35][36].…”
Section: Discussionsupporting
confidence: 72%
“…This finding is in line with findings by Graham et al (2001), Stanley et al (2011) andYong et al (2011) that the spiritual element if applied to a career helps to alleviate stress. The study by Yong et al (2011) shows that after a spiritual program given to nurses in Korea, stress was reduced and spiritual well-being and leadership value increased. Similarly, the study by Hsiao et al (2010) finds that the spiritual health of students can be a mechanism for nursing students to manage their stress, to reduce depressive symptoms and to enhance health-promoting behaviours.…”
Section: Discussionsupporting
confidence: 93%
“…The Maslach Burnout Inventory was used to measure burnout in 5 of the 15 studies. 24,26,27,30,32 It consists of 3 subscales: Emotional Exhaustion, Depersonalization, and Reduced Personal Accomplishment. Yong et al 30 found a significant difference in overall burnout scores between the experimental and control groups.…”
Section: Methodsmentioning
confidence: 99%
“…23 Seven of the 15 studies (46%) used interventions that lasted for 8 weeks, 1 study's intervention lasted 6 weeks, 31 2 studies' interventions lasted 5 weeks, 25,30 1 study's intervention was 4 weeks in length, 28 and 1 study's intervention lasted 1 month. 30 There also was variation in the total length of time the researchers collected data from subjects once the intervention was completed. Oman et al 19,27 collected data on subjects for 19 weeks after the completion of the intervention.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation